Chemical Constituents of Clusia nemorosa Fruits and Evaluation of Antioxidant and Antimicrobial Activity - Ferreira, Rafaela O.; Galo, Jéssica Colodette; Lopes, Paula Monteiro; Moreno, Daniela S. A.; da Silva, Tania Maria Sarmento; de Carvalho, Mário Geraldo (Natural Products Journal, The, 2022)
Background: Clusia nemorosa, popularly known as pororoca, is used in folk medicine to treat inflammation. Objective: The current study was conducted to isolate and identify bioactive compounds from C. nemorosa fruits and to investigate their antimicrobial and antioxidant activities. Methods: The isolation and structural elucidation of the substances were carried out by usual chromatographic techniques and spectroscopic methods, respectively. The antioxidant activity of extracts of C. nemorosa fruits was measured by DPPH assay and antimicrobial activity was evaluated against the microorganisms Staphylococcus aureus, Candida albicans, Cryptococcus neoformans, and Rhizopus oryzae. Results: The chemical investigation of the fruit extract of C. nemorosa led to the identification of two phenolic acids, protocatechuic acid (1) and coumaric acid (6), a flavonoid apigenin (7), glycosyl-β- sitosterol (4), glycosyl-stigmasterol (5), citric acid (3), and the trimethyl citrate ester (2). The fraction in AcOET showed the best scavenging activity of the DPPH radical, with IC50 = 23.50±1.7 μg. mL-1. The extracts were inactive against the tested microorganisms up to 2500 μg. mL-1. Conclusion: With the exception of the steroid glycosyl-β-sitosterol, the substances are described for the first time in the species, and, in addition, we report the promising free radical scavenging activity showing its potential in the treatment of diseases related to oxidative stress.
Keywords: microorganisms